SOCIETY SPEAKING CLUB SEBAGAI SARANA PENINGKATAN KEMAMPUAN KETERAMPILAN KOMUNIKASI BAHASA INGGRIS LISAN UNTUK MASYARAKAT - Rina Astuti Purnamaningwulan; Thomas Wahyu Prabowo Mukti; Catharina Brameswari; Epata Puji Astuti (Universitas Sanata Dharma, 2021)
English oral communication proficiency is one of the absolute needs of adult learners in entering the digital industrialization era 4.0, where opportunities and competitions are more massive. Several limitations that are implemented as a response to the Covid-19 pandemic have made it difficult for most adult learners to practice their English communication skill intensively. This community service program aims to provide adult learners with the opportunities to practice English speaking skill through an interactive webinar and online group discussions. The Society Speaking Club was conducted in four meetings with the topics of mental health, diversity, environment, and entrepreneurship. The topics were selected so as to allow participants to relate the discussions to their life more easily, as well as to be more aware about the recent issues. This community service program has benefited the participants in a way that they became more confident and fluent in communicating their ideas effectively. In addition, the participants admitted that they got new insights on the issues being discussed, and they were called into actions for maintaining mental health, promoting and respecting diversity, preserving the environment, and developing entrepreneurial skills.